Cross-cutting view of current challenges in paediatric solid organ and haematopoietic stem cell transplantation in Europe: the European Reference Network TransplantChild - Jara, P. (Orphanet J Rare Dis, 2020)
The low prevalence of European paediatric transplanted patients and scarcity of resources and expertise led to the need for a multidisciplinary network able to improve the quality of life of paediatric patients and families requiring a solid organ or haematopoietic stem cell transplantation. The European Reference Network (ERN) TransplantChild is one of the 24 ERNs established in a European legal framework to improve the care of patients with rare diseases. ERN TransplantChild is the only ERN focused on both solid organ and haematopoietic stem cell paediatric transplantation, based on the understanding of paediatric transplantation as a complex and highly specialised process where specific complications appear regardless the organ involved, thus linking the skills and knowledge of different organ disciplines. Gathering European centres of expertise in paediatric transplantation will give access to a correct and timely diagnosis, share expertise and knowledge and collect a critical mass of patients and data that increases the speed and value of clinical research outcomes. Therefore, the ERN TransplantChild aims for a paediatric Pan-European, Pan-transplant approach.